2014
DOI: 10.1016/j.amjcard.2014.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Serotonin Reuptake Inhibitors on Bleeding Risk in Patients With Atrial Fibrillation Taking Warfarin

Abstract: Selective serotonin reuptake inhibitor (SSRI) medications have been linked to increased bleeding risk, however, the actual association between warfarin, SSRI exposure, and bleeding risk has not been well-established. We studied the AnTicoagulation and Risk factors In Atrial fibrillation (ATRIA) cohort of 13,559 adults with atrial fibrillation (AF), restricted to the 9186 patients contributing follow-up time while taking warfarin. Exposure to SSRIs and tricyclic antideprssants (TCAs) were assessed from pharmacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 26 publications
3
53
0
Order By: Relevance
“…[8][9][10][11] This has been reported for upper GI bleedings as well as for the risk of cerebral haemorrhage. Second, bleeding events in patients with SSRI or other antidepressant therapy who received a coprescription with NOAC were higher than those recorded for co-medication with VKA.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] This has been reported for upper GI bleedings as well as for the risk of cerebral haemorrhage. Second, bleeding events in patients with SSRI or other antidepressant therapy who received a coprescription with NOAC were higher than those recorded for co-medication with VKA.…”
Section: Resultsmentioning
confidence: 99%
“…In a large community‐based observational AF cohort, we previously found an adjusted relative risk for major hemorrhage of 1.41 (95% CI, 1.04–1.92) with the addition of SSRIs to warfarin 26. Several studies using large national databases have reported that concomitant use of SSRIs with vitamin K antagonists increased the risk of hospitalized bleeding events by roughly 30% to 70%, and a recent nested case‐control study from the United Kingdom Clinical Practice Datalink found an odds ratio of 1.73 (95% CI, 0.89–3.39) for intracranial hemorrhage in patients taking warfarin when SSRIs were added 15, 24, 25, 27.…”
Section: Discussionmentioning
confidence: 99%
“…Further, SSRIs inhibit the cytochrome P450 metabolic pathway, potentially increasing warfarin's effect 21, 22, 23. Several studies have reported that the combination of warfarin and SSRIs leads to an increased risk of major hemorrhage 24, 25, 26, 27, 28. No study has yet examined the possible drug‐drug interaction between SSRIs and non–vitamin K antagonist oral anticoagulants.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the elevated mortality is not known, but SSRIs are preferred to tricyclic antidepressants because of their tolerability and safety profile. The benefits of SSRIs may accrue at the expense of an overall increased bleeding risk . Platelets acquire serotonin from plasma, which is released upon platelet activation to amplify aggregation .…”
Section: Introductionmentioning
confidence: 99%